Development of α‐Gal–Antibody Conjugates to Increase Immune Response by Recruiting Natural Antibodies. (8th March 2019) - Sianturi, Julinton; Manabe, Yoshiyuki; Li, Hao‐Sheng; Chiu, Li‐Ting; Chang, Tsung‐Che; Tokunaga, Kento; Kabayama, Kazuya; Tanemura, Masahiro; Takamatsu, Shinji; Miyoshi, Eiji; Hung, Shang‐Cheng; Fukase, Koichi
Abstract: Cancer treatment with antibodies (Abs) is one of the most successful therapeutic strategies for obtaining high selectivity. In this study, α‐gal–Ab conjugates were developed that dramatically increased cellular cytotoxicity by recruiting natural Abs through the interaction between α‐gal and anti‐gal Abs. The potency of the α‐gal–Ab conjugates depended on the amount of α‐gal conjugated to the antibody: the larger the amount of α‐gal introduced, the higher the level of cytotoxicity observed. The conjugation of antibodies with an α‐gal dendrimer allowed the introduction of large amounts of α‐gal to the Ab, without loss of affinity for the target cell. The method described here will enable the re‐development of Abs to improve their potency. Abstract : α‐Gal‐Antikörper(Ak)‐Konjugate ermöglichen eine starke Erhöhung der zellularen Zytotoxizität, indem sie natürliche Ak durch die Wechselwirkung von α‐gal und anti‐gal‐Aks rekrutieren. Die Wirksamkeit der α‐gal‐Ak‐Konjugate erhöht sich dabei mit der Menge an α‐gal, die mit dem Ak konjugiert ist. Die hier vorgestellte Methode ermöglicht eine Neugestaltung von Ak zur Erhöhung ihrer Wirksamkeit.